E-waste management in achieving SDGS in Negara Brunei Darussalam: Maqasid Shariah Perspective - Deuraseh, Nurdeng; Hashim, Norkhairiah; Raffi, Raihana Mohd; Saini, Haziq (Technium Sustainability, 2024)
‘Electronic waste’, ‘Waste Electrical and Electronic Equipment’ or commonly known as ‘E-waste’ or ‘WEEE’ is referred to any electrical object or equipment that no longer possesses any value which has been disposed of by its owner. As other unused items, E-waste, which has not been used and thrown away as waste without being intended for reuse, becomes becomes a big problem to contemporary life. Due to its complex chemical component and inorganic toxic material, E-waste requires special treatment and management different from that of conventional waste. Incorporating e-waste management into the framework of Maqasid of the Shariah provides a holistic approach to achieving Sustainable Development Goals (SDGs) in Brunei. By harmonizing the protection of religion, life, intellect, progeny and wealth with sustainability principles, this approach not only tackles the environmental challenges associated with e-waste but also ensures the well-being of the community in a manner that is in line with the Islamic teachings. To carry out a detailed analysis of e-waste management in achieving SDGs in Negara Brunei Darussalam, a qualitative approach is adopted in order to fulfil the research objectives and a semi-structured interview method is used by the researchers. A total of 10 employees from 6 organizations (inclusive of both government and private sector) were interviewed. The results have shown issues, problems and threats posed by e-waste with time consuming, health concerns, and a lack of awareness to be the main highlights. Aside, an effort from the government body in introducing the ‘Extender Producer Responsibility (EPR) scheme’ in handling and managing e-waste was also discussed. By nurturing a culture of environmental responsibility, increasing awareness through education and implementing efficient waste management approaches, Brunei can not only address the immediate risks associated with e-waste but also contribute to the global pursuit of the SDGs in a way that is spiritually and materially rewarding.